Perennial summer pasture options in Tablelands environments where drought and soil acidity jeopardise pasture persistence - Richard A. Culvenor; Rebecca S. Stutz; Richard C. Hayes (Grassland Research)
Abstract Background The persistence of summer‐active perennial species is critical for pasture‐fed meat production in the temperate, uniform rainfall environment of south‐eastern Australia. Methods To investigate the limitations of important pasture species under contrasting levels of drought and soil acidity stress, we monitored replicated field plots for persistence and productivity at three sites on the Southern Tablelands over 2–3 years. Results All sites experienced a period of severe drought. At one site, persistence was ranked lucerne > phalaris > Porto cocksfoot > Savvy cocksfoot, tall fescue, chicory > plantain, red clover. Bromes survived via recruitment. Lucerne and chicory were the most productive immediately post‐drought in summer and phalaris and chicory in autumn. Cocksfoot outyielded tall fescue. At a higher‐elevation site, less drought‐tolerant species were more persistent and productive. At a site with deep soil acidity, lucerne failed to persist; chicory performed better but declined with overgrazing during drought. Tall fescue declined severely during drought. Conclusions Lucerne remains the most productive summer option if soil conditions allow its growth, with chicory a potential replacement on acidic soils. Good productivity combined with acid soil tolerance favours cocksfoot over tall fescue. The ability to survive occasional severe drought is an important factor in species choice.